Hitting the right notes: Exploring the relationship between youtube music videos and digital user engagement - Johnny Hadi Raharjo; Rianmahardhika Sahid Budiharseno; Tran Minh Quy (Global Business & Finance Review (GBFR), 2024)
Purpose: This study meticulously explored the complexities of online fan engagement, placing a spotlight on the transformative influence of YouTube content produced by the renowned K-pop group, Aespa, and its subsequent impact on user interactions and the group's prevailing image. Design/methodology/approach: Utilizing a robust text mining methodology, a comprehensive analysis was conducted on 11,039 comments extracted from a specific Aespa YouTube video. This analysis involved the extraction of frequently occurring words, the deployment of a semantic network analysis, and the strategic use of the Co-occurrence network analysis, which collectively provided a profound understanding of fan perceptions and sentiments. Findings: Central to the findings was the revelation of Aespa's groundbreaking concept, which emerged as a cornerstone in captivating and retaining fan engagement. The data illuminated the depth of fans' interest in Aespa's narrative approach, with many expressing admiration for the group's commitment to delivering high-quality productions. Research limitations/implications: Their unique blend of music, narrative, and visual aesthetics resonated deeply with the audience, fostering a sense of loyalty and admiration. However, it's imperative to note that the research's purview was limited, focusing solely on comments from one video. This limitation underscores the potential and need for more expansive datasets in subsequent studies, which could provide a more holistic view of fan engagement across multiple content pieces. Additionally, considering the dynamic nature of the K-pop industry and the rapid shifts in public sentiment, there's an evident need for continuous monitoring and analysis. Originality/value: This investigation not only offers a renewed perspective on the role of digital influence within the vibrant world of K-pop but also accentuates the paramount importance of innovative and distinctive content in amplifying user engagement. It serves as a testament to the evolving landscape of digital influence in the entertainment sector, where content, creativity, and audience engagement intersect in profound ways.
Keywords: 650; Aespa; Digital Influence; K-pop; Fan Engagement; Text Mining; Online Interaction